¿Se encuentra justificada la actual política criminal contra agresores sexuales? (2007)
This essay tries to make a critical approximation to the problematic that offers the current tends of criminal policy about sexual aggressors. Throw the revision of the arguments that support the most recent extraordinary measures to face the sexual aggre